SUPPORTING THE NUMERACY LITERACY SKILLS OF ELEMENTARY SCHOOL STUDENTS - Inne Marthyane Pratiwi; Lisna Apriani; Rinaldo Adi Pratama (Jurnal Pengajaran MIPA, 2020)
Numeracy literacy is an essential part of literacy because in it there is a competency that make student to do reasoning so that it can be used in daily life. The research aims to describe the implementation of classroom-based numeracy literacy, school culture, and community in elementary schools. The research uses a qualitative approach with descriptive methods. The research was conducted on 76 students from 1st grade and 6th students, homeroom teachers of 1st grade and 6th from public elementary schools. Data collection techniques using observation, document analysis, and interviews. The data is analyzed with thematic analysis. The results showed that at least teachers had participated in numeracy literacy training, students' math skills above the minimum criteria, implementation of problem-based learning and projects, but there were limited resources. Numeracy literacy based on school culture shows the lack of variation of numeration literacy books so that the library as the center of literacy activities has not been maximized. The numeracy literacy of the community base shows that there is no public space used for numeracy literacy and sharing sessions that start running. One of the efforts to optimize numeracy literacy by providing training to teachers. ABSTRAKLiterasi numerasi merupakan bagian literasi yang sangat penting, karena di dalamnya terdapat kompetensi yang mengasah individu untuk melakukan penalaran sehingga dapat digunakan dalam kehidupan sehari-hari. Penelitian bertujuan untuk mendeskripsikan implementasi literasi numerasi berbasis kelas, budaya sekolah, dan masyarakat di sekolah dasar. Pendekatan penelitian menggunakan kualitatif dengan metode deskriptif. Penelitian dilaksanakan terhadap 76 siswa kelas 1 dan 6 serta guru kelas 1 dan 6 sekolah dasar negeri. Teknik pengumpulan data menggunakan observasi, analisis dokumen, dan wawancara. Data dianalisis dengan analisis tematik. Hasil penelitian menunjukkan pada literasi numerasi basis kelas setidaknya guru pernah mengikuti pelatihan literasi numerasi, kemampuan matematika siswa di atas kriteria minimum, terlaksananya pembelajaran berbasis masalah dan proyek, namun terdapat keterbatasan sumber daya. Literasi numerasi basis budaya sekolah menunjukkan kurangnya variasi buku literasi numerasi sehingga perpustakaan sebagai pusat kegiatan literasi keberadaannya belum maksimal. Adapun literasi numerasi basis masyarakat menunjukkan belum adanya ruang publik yang digunakan untuk literasi numerasi dan sharing session yang mulai berjalan. Salah satu upaya optimalisasi literasi numerasi dengan memberikan pelatihan kepada guru.